KEMAMPUAN PENILIK DALAM MELAKSANAKAN TUGAS POKOK DITINJAU DARI KEPUTUSAN MENPAN NO.15/KEP/MENPAN/3/2002 - Baso Intang Sappaile (Jurnal Ilmiah Visi, 2007)
The decentralization policy stipulated in the Constitution of Number 22 of 1999 gives impact to many aspects of government management including in education. This research investigates the assessor’s competence in implementing their main tasks based on the decree of Number 15/KEP/MENPAN/3/2002 and the obstacles in implementing the decree. The research conducted in East Java covering four districts used qualitative approach and the data were collected by interview and document study. The result of this research concludes that the assessor’s competence has not completely met the requirements stated in the Minister’s decree. Local government has given support in implementing the Minister’s decree. However, the problems faced include the lack of assessors’ competences, unclear criteria for professional assessor’s formation based on work load, and the inability of the assessors to count their working credits.